Intrasexual Competition and Height in Adolescents and Adults - Fernandez-Tapia, A (SAGE Publications Inc., 2018)
Intrasexual competition can be defined as the struggle between members of one sex to increase their access to members of the other sex as sexual partners. In our species, height is a sexually dimorphic trait probably involved in both intrasexual and intersexual selective processes. In the present research, we examined the relationship between height and individual differences in intrasexual competitiveness (i.e., the tendency to view same-sex interactions in general in competitive terms) in two populations of adolescents and adults of both sexes in Chile. According to our first prediction, among both adolescent and adult men, height was negatively associated with intrasexual competitiveness. In contrast, among women, height was not linearly nor quadratically related with intrasexual competitiveness as previously reported. Finally, adolescent men and women showed increased levels of intrasexual competitiveness compared to adult same-sex counterparts. Our results suggest that height is a relevant trait in mating competition among men. The lack of relationship between height and intrasexual competitiveness in women may suggest that the role of height in women mating competition may be more complex and mediated by other variables. © 2018, © The Author(s) 2018.